Foreign exchange operations : master trading agreements, settlement, and collateral - DeRosa, David F.; Wiley eBooks (Hoboken : Wiley, 2013)
The ultimate nuts-and-bolts guide to foreign exchange operations The foreign exchange landscape is particularly risky since so much of the world is unregulated and takes place over the counter (off exchange). Brilliant traders and money managers who are profitable may find themselves underperforming, or worse, losing, simply because they failed to establish strong operations. In this book, David DeRosa provides industry players with everything they need for strong operational functions from all the types of trades to execution, master trading agreements, documentation, settlement, mar.
Preface -- Acknowledgments -- About the author -- Introduction to foreign exchange -- Options on foreign exchange -- How trades are executed and confirmed -- Foreign exchange settlement -- References -- Index.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Foreign exchange; Commercial treaties; International trade; BUSINESS & ECONOMICS -- Finance; Commercial treaties; Foreign exchange; International trade; Commercial treaties; Electronic books